Statistical Convergence of Sequences of Functions in Intuitionistic Fuzzy Normed Spaces - Karakaya, Vatan; Simsek, Necip; Erturk, Muzeyyen; Gursoy, Faik (HINDAWI LTD, 2012)
The purpose of this work is to investigate types of convergence of sequences of functions in intuitionistic fuzzy normed spaces and some properties related with these concepts.
Keywords: Mathematics